2014
DOI: 10.1071/sb13045
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the holly grevilleas (Proteaceae) based on nuclear ribosomal and chloroplast DNA

Abstract: Abstract. The holly grevilleas are an informal grouping of 15 species (19 taxa) of woody shrubs from south-eastern Australia, with a centre of distribution in central to western Victoria. Many of the species are narrowly endemic. The present study is the first molecular-phylogenetic analysis of the group, with the aim of providing an evolutionary framework for assessing species-level taxonomy and conservation priorities. Analyses using the nrDNA internal transcribed spacer (ITS) regions were complicated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Other studies (for example, [ 12 , 15 ]) have also indicated that ITS is an informative marker for DNA barcoding of grasses. However, the presence of multiple paralogous ITS copies [ 54 ], may complicate the interpretation of genetic distances among and within species. For this reason we consider its use, alongside other markers, representing chloroplast and nuclear genomes, to be more optimal than its use individually.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (for example, [ 12 , 15 ]) have also indicated that ITS is an informative marker for DNA barcoding of grasses. However, the presence of multiple paralogous ITS copies [ 54 ], may complicate the interpretation of genetic distances among and within species. For this reason we consider its use, alongside other markers, representing chloroplast and nuclear genomes, to be more optimal than its use individually.…”
Section: Discussionmentioning
confidence: 99%
“…Our dataset included 66 accessions of Corymbia (representing all taxonomic sections), 15 of Angophora (9 of 10 species), 31 of Eucalyptus (the same species as in the cpDNA dataset, representing major lineages), two of Stockwellia , one of Eucalyptopsis , three of Allosyncarpia , and one of Arillastrum (used as outgroup). Partial sequences, or those identified as spacers associated with pseudogenes using established criteria [ 59 , 60 , 61 , 62 ], were excluded from analyses. We used existing nrDNA sequences for analyses, rather than assembling novel sequences from our current genomic data for Corymbia , because of the presence of substantial within-genome variation in our samples (in line with previous reports [ 38 , 59 , 60 ]), and associated difficulties in separating and assembling sequences of the various paralogues/alleles, which is a challenging task worthy of separate investigation and discussion.…”
Section: Methodsmentioning
confidence: 99%
“…Results from techniques, not then available to McGillivray, but developed subsequently, to examine phylogeny and analyse relationships, have repeatedly shown that morphology is not necessarily a reliable guide to relationships. Holmes et al (2014) resolved Grevillea montis-cole subsp. brevistyla R.V.Sm.…”
Section: Pierre-denis Pépinmentioning
confidence: 99%